SARCASM AND THE TRANSLATION QUALITY IN THE SUBTLE ART OF NOT GIVING A FUCK BOOK - Zawawi, Moh.; Maghfiroh, Devi Laila (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2020)
Sarcasm is a harsher style of satire in hurtful jokes with a specific purpose. Sarcasm is the dominant language style used in Mark Manson's The Subtle Art of Not Giving A Fuck. This study aims to identify sentence forms of sarcasm and analyze the translation quality of sarcastic expressions. This translation study employs a qualitative descriptive design. The research data takes the form of sentences containing sarcasm and its translation. The data is collected through document analysis, interviews, and focus group discussions. The results showed four types of sarcasm in the book The Subtle Art of Not Giving A Fuck, including ridicule, satire, proximity, and humor. Besides, the translation quality of the book The Subtle Art of Not Giving A Fuck has a high level of accuracy, acceptability, and readability, evidenced by the proper use of eleven translation techniques applied by the translator to 145 data. The frequent techniques contributing to the quality of translation are compensation, adaptation, transposition, and modulation techniques.